The racialization of motive: understanding the framing of East Asian crime in video games - Pfliger, Amber (My University, 2019)
To gain a comprehensive understanding as to how East Asian crime is framed in video games, the origin stories of three video game protagonists were examined. To accomplish this, a coding scheme was utilized to draw themes on protagonist motive, which was then compared to Liu’s Asian paradigm theory (Liu, 2016). By doing so, it demonstrated the homogenization of motive in relation to East Asian culture and emphasized honour as a racially explicit motive. These findings are discussed concerning accurate cultural framing and the development of the racialized other.
Presented on April 23, 2019 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: video games; East Asian culture; racialization